1997
DOI: 10.1021/tx960048j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substituents in Fluorobenzene Derivatives on the Cytochrome P450-Catalyzed Hydroxylation at the Adjacent Ortho Aromatic Carbon Center

Abstract: In a previous study, the in vivo cytochrome P450-catalyzed regioselectivity of aromatic ring hydroxylation for a series of (poly)fluorobenzenes could be quantitatively predicted by the calculated frontier orbital density distribution in the aromatic ring [Rietjens et al. (1993) Biochemistry 32, 4801-4812]. However, the relative small fluorine, its size almost comparable to a hydrogen, is not expected to influence the regioselectivity of aromatic hydroxylation due to steric hindrance. The aim of the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Some researchers have correlated the regiospecificity of cytochrome P450-catalysed hydroxylation of aromatic compounds with calculated frontier orbital density distribution (Koerts et al, 1997, Rietjens et al, 1993. Here, calculated frontier orbital density distributions at high-level computations (see supporting information for details) confirm the regiospecificity of CYP-catalysed hydroxylation for compounds 1-3 and 5 where the highest HOMO densities are found at the 4' carbon sites in these starting molecules.…”
Section: Mammalian Biotransformation Of Fluorophenyl Pyridine Carboxysupporting
confidence: 61%
“…Some researchers have correlated the regiospecificity of cytochrome P450-catalysed hydroxylation of aromatic compounds with calculated frontier orbital density distribution (Koerts et al, 1997, Rietjens et al, 1993. Here, calculated frontier orbital density distributions at high-level computations (see supporting information for details) confirm the regiospecificity of CYP-catalysed hydroxylation for compounds 1-3 and 5 where the highest HOMO densities are found at the 4' carbon sites in these starting molecules.…”
Section: Mammalian Biotransformation Of Fluorophenyl Pyridine Carboxysupporting
confidence: 61%
“…The mass spectra were obtained on an Hewlett-Packard G1800A GC-MS system consisting of an HP 5971 mass-selective detector and an HP 5890 Series II gas chromatograph. The structure of the obtained compounds was confirmed by the 1 H and 19 F NMR and mass spectra which were consistent with published data for 2-fluoro-1,3,5-trimethylbenzene, 2,4-difluoro-1,3,5-trimethylbenzene [39], 3-fluoro-1,2,4,5-tetramethylbenzene [39], 1-fluoro-2,3,4,5,6-pentamethylbenzene [40], 1-fluoro-2,4-dimethylbenzene, 2-fluoro-1,3-dimethylbenzene* [41], 2-and 4-fluorophenols [41][42][43], 2,4-difluorophenol [42], 2-fluoro-4-methylphenol [41], 2-fluoro-1-methoxy-4-methylbenzene, 4-chloro-2-fluoro-1-methoxybenzene [19], 2-fluorobenzene-1,3-diol, 4-fluorobenzene-1,3-diol, 4,6-difluorobenzene-1,3-diol [29,44], 1-fluoronaphthalen-2-ol [31], 2-and 4-fluoronaphthalen-1-ols [23], and 2-and 4-fluoro-1-methoxybenzenes [19,41].…”
Section: Methodsmentioning
confidence: 99%
“…The bioactivation or elimination of halobenzene derivatives such as fluorobenzene is influenced by the regioselectivity and extent of CYP450 catalyzed monooxygenation, which in turn is caused by the size of the substituent [208]. It is demonstrated that chlorine and cyano substitution at C-4 position of fluorobenzene did not hamper hydroxylation at the positions ortho to the C-4 carbon atom whereas bromo and iodo substitution reduced it.…”
Section: Ipso-substitutionmentioning
confidence: 99%